The Nexus of Training, Employee Commitment and Employee Performance in Nepalese Commercial Banking Sector (The Batuk, 2020)
This research attempts to measure the nexus of training, employee commitment, and employee performance in the Nepalese commercial banking sector. Descriptive and causal research design is used to achieve the objectives of the research. Structured questionnaires were made, and the survey was done to collect primary cross-sectional data. Employees of the commercial banks in Kathmandu Valley who have been involved in the training program at least one time are included in the survey. Judgmental sampling was taken. This research confirmed that the training need assessment, mode of training, and training feedback significantly influence employee commitment, and employee commitment influences employee performance in commercial banks. So, bank managers must accept the nexus of training in employee commitment and employee performance.